Adult nutritional stress decreases oviposition choosiness and fecundity in female butterflies. (12th March 2019) - Jaumann, Sarah; Snell-Rood, Emilie C
Abstract: Despite the benefits of careful decision-making, not all animals are choosy. One explanation is that choosiness can cost time and energy and thus depend on nutrition. However, it is not clear how allocation to choosiness versus other components of life-history shifts in the face of nutritional stress. We tested 2 hypotheses about the effects of nutritional stress on choosiness and other life-history traits: 1) poor nutrition leads to compensatory shifts in life-history strategy towards greater investment per offspring in terms of choosy oviposition behavior and egg resources, and 2) poor nutrition negatively affects a range of life-history traits. Cabbage white butterfly ( Pieris rapae ) females were reared under low or high nutrition conditions during the larval and adult stage in a fully factorial design. Choosiness was quantified as avoidance of conspecific models during oviposition. Adult life-history traits included egg number, egg size, and thorax protein. Females that experienced nutritional stress as adults were less choosy and less fecund, in support of the second hypothesis. Yet females that were stressed as larvae invested more in thorax muscle, consistent with the first hypothesis. Overall, adult nutritional stress decreased investment in multiple reproductive traits, including a behavioral trait, but larval stress increased investment in flight, potentially to disperse away from nutritionally poor environments. Abstract : Nutritional stress has varying effects depending on life stage and trait of interest. We show that in female butterflies, poor adult nutrition reduces choosy egg-laying behavior and egg number, while poor larval nutrition increases protein in adult wing muscles, which could enhance flight. Females might compensate for poor larval nutrition by eating more food or by flying to a better environment. If neither strategy is possible, females without adequate access to food may suffer reproductive consequences.